Strategi Menanamkan Karakter Disiplin Melalui Budaya Sekolah - Rizki Wulan Ningsih; Ratna Sari Dewi; Patra Aghtiar Rakhman (Pusat Riset dan Inovasi Nasional, 2025)
Discipline character is one of the factors that significantly influences the formation and development of morals, behavior, character, and individual traits. This study aims to describe the strategy of instilling disciplinary character through school culture at SDN Keroncong 1, explain the disciplinary character through school culture at SDN Keroncong 1, and describe the evaluation of the strategy for instilling disciplinary character through school culture at SDN Keroncong 1. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation. The findings of this study indicate that 1) the strategy of instilling disciplinary character through school culture describes a positive impact because discipline is formed through a good school culture, so students adapt through relevant and need-based learning. 2) disciplinary character through school culture explains one way to adapt by looking at examples and role models who have successfully adapted to the school environment, 3) the evaluation of the strategy for instilling disciplinary character through school culture describes the involvement of all school stakeholders that can create a school culture that supports the formation of healthy social relationships, disciplined students tend to be more cooperative, and able to maintain beneficial interactions.